Rancangan Sistem Informasi Pengajuan Kuliah Kerja Praktek Dan Penentuan Dosen Pembimbing Dengan Metode AHP - Nadiatul Khairiyah; Agnes Novita (STMIK Banjarbaru, 2021)
The Faculty of Information Technology, Perbanas Institute, is still processing work assignments for students (read: KKP), as well as manual submissions for “the KKP” supervisors. To determine the supervisor, the Head of the Study Program is only supported by manually processed data. During guidance with the supervisor, both students and lecturers record the guidance material on paper so that it is at risk of being lost or scattered. In addition, the evaluation process for the Job Training Lecture activity is still written on paper, so that the assessment is not confidential. This paper presents the design of an information system to process the application for the Practical Work Lecture program and the determination of student supervisors. Applications developed using the Analytical Hierarchy Process (AHP) model and running in Web Base mode. The main feature of the application is in the form of a computerized name recommendation system for the internship supervisor.Keywords: Information System Design, Practical Job Lecture, Analytical Hierarchy Process ABSTRAK. Fakultas Teknologi Informasi Perbanas Institute masih memproses pengajuan Kuliah Kerja bagi mahasiswa, serta pengajuan dosen pembimbing (KKP) secara manual. Untuk menentukan dosen pembimbing, Ketua Proram Studi hanya didukung oleh data-data yang diproses secara manual. Saat bimbingan dengan dosen pembimbing, baik mahasiswa maupun dosen mencatat materi bimbingan pada kertas sehingga beresiko hilang atau tercecer. Selain itu, proses penilaian aktivitas Kuliah Kerja Praktek masih dituangkan pada kertas, sehingga membuat penilaian tidak bersifat rahasia. Paper ini menyajikan Rancangan sistem informasi untuk memproses pengajuan program Kuliah Kerja Praktik dan penentuan pembimbing mahasiswa. Aplikasi yang dikembangkan menggunakan model Analytical Hierarchy Process (AHP) dan berjalan dalam moda Web Base. Fitur utama aplikasi berupa sistem rekomendasi nama dosen pembimbing Kuliah Kerja Praktek Secara terkomputerisasi.Kata kunci: Rancangan Sistem Informasi, Kuliah Kerja Praktek, Analytical Hierarchy Process